Meningkatkan Kemampuan Berhitung Siswa Tunanetra dengan Menggunakan Kalkulator AI Sebagai Media Interaktif - Alamsyah, Moch Albani; Sarnita, Fitria; Syariffudin, Syariffudin (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This research discusses the use of AI calculators as interactive media in mathematics learning for blind students. Apart from that, AI calculators can also increase students' desire to participate more actively in mathematics learning. However, it should be noted that the use of AI calculators as interactive media cannot yet replace the role of teachers in teaching mathematics for blind students. Teachers still need to provide guidance and assistance to blind students in using AI calculators and provide material and practice math questions that suit the abilities of blind students. This research was conducted using a qualitative descriptive method with data collection through observation, interviews and written tests. The research results show that using an AI calculator can significantly improve the numeracy skills of blind students. Therefore, it is recommended that AI calculators be used as interactive media that can be applied in mathematics learning for blind students to improve their numeracy skills and make it easier to understand mathematical concepts and solve mathematical problems